2016
DOI: 10.1111/zph.12254
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Hepatitis E in Selected Population Groups in Croatia: A Prospective Pilot Study

Abstract: Hepatitis E has become an emerging infection in many European countries. We analysed the prevalence of hepatitis E virus (HEV) infection in selected population groups in Croatia. Overall HEV IgG seropositivity was 5.6%, while 1.9% participants showed IgM antibodies suggestive of recent infection. No IgM-positive sample was positive for HEV RNA. HEV IgG antibodies were most prevalent in alcohol abusers (8.9%) and war veterans (8.6%), compared with 6.1% among injecting drug users and 2.7% in healthcare professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 49 publications
(79 reference statements)
5
21
1
Order By: Relevance
“…As has been reported in many studies, age was significantly associated with the presence of anti‐HEV IgG in this study . The seroprevalence increased with age and those aged >35 years were three times more likely to be anti‐HEV IgG positive than those aged ≤35 years among our sample of person who use crack.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…As has been reported in many studies, age was significantly associated with the presence of anti‐HEV IgG in this study . The seroprevalence increased with age and those aged >35 years were three times more likely to be anti‐HEV IgG positive than those aged ≤35 years among our sample of person who use crack.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, never use of condom in anal intercourse was associated with past‐HEV infection in the univariate analysis but not in the multivariate analysis. There is no direct evidence that HEV is transmitted by sexual contact, although some studies have shown high seroprevalence of anti‐HEV‐IgG in homosexual men . Persons who use crack spend long periods in drug use settings, they may be more predisposed to acquiring HEV infection through sharing personal utensils with poor hand hygiene allowing the risk of person‐to‐person transmission of infections .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Croatia, autochthonous he was recognized in 2012 (ČIVLJAK et al, 2013). the seroprevalence in tested non a-C hepatitis patients with hepatic disorders was 10.70%, (ĐAKOVIĆ RODE et al, 2014), and 5.6% in asymptomatic individuals (VILIBIĆ-ČAVLEK et al, 2016).…”
Section: Serology Resultsmentioning
confidence: 99%